1997
DOI: 10.1161/01.hyp.29.1.291
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Adhesion Molecules and Leukocyte Integrins in Preeclamptic Patients

Abstract: Endothehal cell activation 1s Important m the pathogenesls of preeclampsla, however, the nature of the actlvatlon IS unknown We investigated 22 patients with preeclampsla, 29 normotensive pregnancies, and 18 nonpregnant women to test the hypothesis that serum from preeclamptlc patients induces expresslon of mtercellular adhesion molecule-1 (ICAM-1) and vascular adhesion molecule-l (VCAM-1) and stimulates mtracellular free calcium concentrations [Ca"], m cultured endothehal cells We then asked whether the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 34 publications
4
49
0
4
Order By: Relevance
“…Impaired placentation and concomitant placental hypoxia induce the release of various factors in the maternal circulation that lead to enhanced endothelial permeability (25), altered expression of adhesion molecules, and increased intracellular free calcium content in the endothelium (26). VEGF is one of the most important growth and survival factors of endothelial cells, and free VEGF is reduced in the plasma of preeclamptic women (15), whereas its soluble receptor sFlt-1 is elevated in the serum of preeclamptic women (8).…”
Section: Discussionmentioning
confidence: 99%
“…Impaired placentation and concomitant placental hypoxia induce the release of various factors in the maternal circulation that lead to enhanced endothelial permeability (25), altered expression of adhesion molecules, and increased intracellular free calcium content in the endothelium (26). VEGF is one of the most important growth and survival factors of endothelial cells, and free VEGF is reduced in the plasma of preeclamptic women (15), whereas its soluble receptor sFlt-1 is elevated in the serum of preeclamptic women (8).…”
Section: Discussionmentioning
confidence: 99%
“…Specific defects in resistance artery endothelium from women with preeclampsia have been shown (65). Supportive evidence for NO deficiency in preeclampsia has recently been obtained from the reduced uterine perfusion pressure rat model (66).…”
Section: Endothelium-derived Relaxing Factors and Their Inhibitorsmentioning
confidence: 90%
“…Haller et al (65,66) observed that a circulating factor in preeclamptic women caused endothelial cells to express surface adhesion molecules and made endothelial cell layers more permeable. The latter process involved the activation of protein kinase C. Wallukat et al (67) subsequently identified circulating autoantibodies that are capable of activating the angiotensin II (Ang II) AT1 receptor.…”
Section: Circulating Autoantibodiesmentioning
confidence: 99%
“…10,11 Recently, we observed that circulating antibodies to a vascular receptor might be responsible for the hypertension observed in preeclampsia. 12 We found that the IgG fraction from preeclamptic women contains an angiotensin-1 receptor autoantibody (AT 1 -AA) that stimulates the AT 1 receptor.…”
Section: See Page 2335mentioning
confidence: 99%
“…10 Endogenous peroxidase was inactivated by immersing the sections in methanol containing 0.6% H 2 O 2 for 10 minutes. After the standard steps, the sections were developed in 3-amino-ethylcarbazole until a red/brown reaction product could be seen.…”
Section: Immunohistochemistrymentioning
confidence: 99%